2010
DOI: 10.1136/bcr.02.2010.2707
|View full text |Cite
|
Sign up to set email alerts
|

Benign schwannoma of the tonsil

Abstract: SummaryThe case of a rare tumour in a rare location is presented, and important aspects of the management of similar clinical scenarios are highlighted. Tonsillar schwannoma is a slow growing lesion presenting in the third to fifth decade of life. Histological diagnosis is made through the identification of Antoni A (Verocay bodies) and Antoni B cells with S-100 expression. A 24-year-old man presented with a 5 cm right tonsillar tumour causing dysphagia and dysphonia for 6 weeks. Tonsillar schwannoma can be di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…In our review of the world literature, we found only 6 previously reported cases of tonsillar schwannoma; chronologically, these 6 cases involved a 40-year-old patient whose sex was not reported, 5 a 13-year-old girl, 6 a 69-year-old woman, 7 a 38-year old man, 8 a 23-year-old woman, 9 and a 24-year-old man. 10 In this article, we report a new case of tonsillar schwannoma in an adult.…”
Section: Introductionmentioning
confidence: 95%
“…In our review of the world literature, we found only 6 previously reported cases of tonsillar schwannoma; chronologically, these 6 cases involved a 40-year-old patient whose sex was not reported, 5 a 13-year-old girl, 6 a 69-year-old woman, 7 a 38-year old man, 8 a 23-year-old woman, 9 and a 24-year-old man. 10 In this article, we report a new case of tonsillar schwannoma in an adult.…”
Section: Introductionmentioning
confidence: 95%
“…It is rarely found in the oral cavity, oropharynx, and palatine tonsil. 1 The tumor may present at the second and fourth decade of life with favoritism to either sex. Here we report a case of tonsillar Schwannoma in a 32-year-old female.…”
Section: Introductionmentioning
confidence: 99%